2022
DOI: 10.1186/s12929-022-00832-z
|View full text |Cite
|
Sign up to set email alerts
|

CLEC5A and TLR2 are critical in SARS-CoV-2-induced NET formation and lung inflammation

Abstract: Background Coronavirus-induced disease 19 (COVID-19) infects more than three hundred and sixty million patients worldwide, and people with severe symptoms frequently die of acute respiratory distress syndrome (ARDS). Recent studies indicated that excessive neutrophil extracellular traps (NETs) contributed to immunothrombosis, thereby leading to extensive intravascular coagulopathy and multiple organ dysfunction. Thus, understanding the mechanism of severe acute respiratory syndrome coronavirus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
1
22
1
Order By: Relevance
“…In our findings with hamster samples, the animals were challenged with SARS‐CoV‐2 to monitor the kinetic of CLEC5A gene expression 15 days after infection, and the data showed that after 3 days of viral infection CLEC5A gene is expressed in blood samples. Similar results were seen by other authors, in which CLEC5A markers were detected in murine samples during pulmonary mycobacterial infection and other viral infections, but it was not detected in healthy samples 32,37–39,42,43 . In addition, some studies mentioned that inflammatory cells are detected in the lung at 2–10 days postinfection with SARS‐CoV‐2 particles, being part of the disease's pathology in hamster models 42,43 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our findings with hamster samples, the animals were challenged with SARS‐CoV‐2 to monitor the kinetic of CLEC5A gene expression 15 days after infection, and the data showed that after 3 days of viral infection CLEC5A gene is expressed in blood samples. Similar results were seen by other authors, in which CLEC5A markers were detected in murine samples during pulmonary mycobacterial infection and other viral infections, but it was not detected in healthy samples 32,37–39,42,43 . In addition, some studies mentioned that inflammatory cells are detected in the lung at 2–10 days postinfection with SARS‐CoV‐2 particles, being part of the disease's pathology in hamster models 42,43 …”
Section: Discussionsupporting
confidence: 85%
“…Similar results were seen by other authors, in which CLEC5A markers were detected in murine samples during pulmonary mycobacterial infection and other viral infections, but it was not detected in healthy samples. 32,[37][38][39]42,43 In addition, some studies mentioned that inflammatory cells are detected in the lung at 2-10 days postinfection with SARS-CoV-2 particles, being part of the disease's pathology in hamster models. 42,43 F I G U R E 4 In silico interaction between CLEC5A and spike protein (SARS-CoV-2).…”
Section: Discussionmentioning
confidence: 99%
“…The tropism of SARS-CoV-2, defined by entry into cells via the widely expressed ACE2 receptor, makes it possible for the infection to spread to different organs, such as the lung, heart, intestine, liver, and brain. This can generate acute as well as chronic damage in various districts [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Discussionmentioning
confidence: 99%
“…During viral replication of SARS-CoV-2, double-stranded (ds) RNA is also produced, which binds TLR3 and activates TIR domain-containing adapter protein, inducing the interferon β (TRIF) pathway. Considering the protein components of SARS-CoV-2, the ability of TLR2 to bind the E (envelope) protein and the subsequent activation of MyD88 in association with inflammation in the lung district have also been demonstrated [ 36 , 37 ]. The combination of different viral proteins—for example, those released from endosomes and those translated by reading viral genomic RNA—are recognized by RLRs that associate with MDA-5 and MAVS and activate IRF3/7, leading to the secretion of IFN-α/β [ 38 , 39 ].…”
Section: Covid-19: From Infection To Host Antiviral Responsementioning
confidence: 99%
“…A recent study shows that SARS-CoV-2 viral proteins induce NET formation via a Syk-dependent pathway of downstream signaling molecules of C-type lectin receptors ( 26 ). Further study shows that EVs released from SARS-CoV-2-activated platelets induce robust formation of NET via CLEC5A and TLR2, which in turn enhance thrombosis ( 27 ).…”
Section: Mechanisms Of Inflammation In Covid-19mentioning
confidence: 99%